PENERAPAN PRINSIP GOOD CORPORATE GOVERNANCE PADA KASUS TATA KELOLA MINYAK MENTAH DAN PRODUK KILANG DI PT PERTAMINA PATRA NIAGA: Implementation of Good Corporate Governance Principles in Crude Oil and Refined Product Governance at Pertamina Patra Niaga Case - Malaka Hirarki Rajasa; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2026)
The principles of Good Corporate Governance and fiduciary duty constitute the fundamental basis for the management of company by the Board of Directors, as stipulated in Article 97 paragraphs (2) and (3) of Law Number 40 of 2007 on concerning Limited Liability Companies. This study focuses on accountability of the Board of Directors of PT Pertamina Patra Niaga in the case of crude oil and refined product governance, which resulted in losses to the company and were classified as state losses, particularly in relation to the failure to implement Good Corporate Governance principles. The research employs a normative legal research with a principles-based approach, utilizing secondary data analyzed qualitatively through deductive reasoning. The findings and conclusions indicate potential violations of fiduciary duty in the form of negligence in the principle of prudence, weak transparency, and inadequate internal supervision, thereby exposing the Board of Directors to possible personal liability and the loss of managerial discretion protection. These findings emphasize that the implementation of Good Corporate Governance principles serves as a key parameter in determining the scope of authority and responsibility of the Board of Directors.